2020
DOI: 10.1002/jemt.23679
|View full text |Cite
|
Sign up to set email alerts
|

The optical density and topography characterizations of MWCNTs on Ni‐Cu/ a‐C:H substrates with different copper percentage

Abstract: In this article, the Ni-Cu nanoparticles (NPs) in the amorphous carbon hydrogenated thin films with different copper percentage by co-deposition of RF-plasma enhanced chemical vapor deposition were prepared using acetylene gas and Ni and Cu targets. The films deposited with 5% Cu have minimum value of the average diameter of Multi-walled Carbon Nanotubes, MWCNTs, in about of 100 nm. It can be seen that the lateral size values of the nanoparticles for films with 5% Cu have minimum value of 5.34 nm. Films deposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…where the order number m is an integer for maxima and a half integer for minima, this value of m can now be used, along with n 1 , to calculate the "order number" m °for the different extremes using relationship (18). In previous reports (Rahimi et al, 2020a(Rahimi et al, , 2020bDalouji et al, 2020aDalouji et al, , 2020bDalouji et al, 2019), the optical transmittance and reflectance spectrum for films were showed. Now, the dependence of n on photon energy of the study thin films is shows in Figure 10(b).…”
Section: Determination Of the Refractive Index And Film Thicknessmentioning
confidence: 95%
See 3 more Smart Citations
“…where the order number m is an integer for maxima and a half integer for minima, this value of m can now be used, along with n 1 , to calculate the "order number" m °for the different extremes using relationship (18). In previous reports (Rahimi et al, 2020a(Rahimi et al, , 2020bDalouji et al, 2020aDalouji et al, , 2020bDalouji et al, 2019), the optical transmittance and reflectance spectrum for films were showed. Now, the dependence of n on photon energy of the study thin films is shows in Figure 10(b).…”
Section: Determination Of the Refractive Index And Film Thicknessmentioning
confidence: 95%
“…In these samples, the shift in absorption edge was increased from 3.15 eV (l ¼ 393.6 nm) to 3.05 eV (l ¼ 406.5 nm) and 3.03 eV (l ¼ 408.7 nm) to 2.92 eV (l ¼ 424.6 nm) for CZO films, respectively. The optical density, D opt of samples can be obtained from the following formula (Dalouji et al, 2020a(Dalouji et al, , 2020b):…”
Section: Optical Studies 221 Optical Absorption Coefficientmentioning
confidence: 99%
See 2 more Smart Citations
“…These interesting and unique properties of copper have led to many applications in architectures, auto-motives, bio-medicals, solar cells, sensors, catalysis, optoelectronics and etc [6,7]. Copper-based nanoparticles are synthesized by a variety of chemical and physical methods such as chemical precipitation, sol-gel, sonochemical, hydrothermal, electrochemical, photochemical, biological method, mechanical-ball milling, pulse laser ablation, micro-emulsion, thermal decomposition, microwave synthesis method and etc [8, 9,[18][19][20][21][22][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%